State reclamation credit in the system of legislation in Ukrainian lands at the XIX – XX centuries - Selikhov, Dmytro; Derevyanko, Bogdan; Armash, Nadiia; Severinova, Oleksandra; Orlova, Iryna (Linguistics and Culture Review, 2021)
The article analyses the process of evolution of land reclamation legislation in general and land reclamation credit in particular of the Russian Empire of the late XIX – early XX centuries. This period of Ukrainian history is known for the sharp aggravation of the agrarian issue, which was influenced by both internal and external factors associated with the global agrarian crisis. It was this circumstance that influenced the position of the central authorities, which since the end of the XIX century have been actively looking for a way out of the crisis, using land reclamation legislation along with other methods. In this regard, the authors paid special attention to the reclamation laws of May 6, 1896, May 29, 1900, and May 20, 1902, as well as the activities of the "local committees on the needs of the agricultural industry" of the Ukrainian provinces in 1902-1903 in the corresponding direction of work. The period of the Stolypin agrarian reform, when land reclamation legislation became an integral part of a broader government program to improve the quality of agricultural land and Land Management, is also not ignored.